214k views
2 votes
5(6-i)+(6-i)(3-i). show work.

1 Answer

5 votes

47 -14i

You can work this out in the straight-forward way, or you can recognize that (6-i) is a common factor. In the latter case, you have ...

... = (6-i)(5 + 3-i)

... = (6 -i)(8 -i)

This product of binomials is found in the usual way. Each term of one factor is multiplied by each term of the other factor and the results summed. Of course, i = √-1, so i² = -1.

... = 6·8 -6i -8i +i²

... = 48 -14i -1

... =

_____

A suitable graphing calculator will work these complex number problems easily.

5(6-i)+(6-i)(3-i). show work.-example-1
User Tiger Peng
by
6.5k points